The Mediating Role of Internet Addiction in the Relationship Between Loneliness and Depression Among Adolescents - Buntaran, Firman Alamsyah Ario; Kadir, Nor Ba’yah Abdul; Zakaria, Siti Marziah (Kuras Institute, 2025)
Loneliness and internet addiction (IA) are risk factors for depression. Internet addiction and depression among adolescents have recently increased in prevalence globally and are expected to continue to increase. However, there is no clear line between internet addiction and depression as to why it occurs. Previous research on the relationship between loneliness and depression in adolescents involved IA as a mediator, and the results of the study showed that IA can be a partial mediator between loneliness and depression. However, in Indonesia, there has been no similar research regarding IA as a mediator and explaining the relationship between these variables. Previous studies show that lonely individuals show high levels of IA. It also causes depression in adolescents. The relationship is still not fully explained. The results of a study involving 732 adolescents in Indonesia, high school students aged 14 to 19 years, actively using the internet, and owning smartphones show that there is partial mediation of IA in the relationship between loneliness and depression in adolescents. Loss of control (LoC) is a dimension that is strongly associated with depression and loneliness. The amount of time spent on the Internet is also linked to loneliness and depression. The study found that girls were more likely to experience depression and loneliness compared to boys. These findings provide important information for parents and schools, and interventions related to these findings can be of serious concern.